Postmenopausal Patients With Endometrial Cancer of Type 1 Have Elevated Serum Estradiol Levels in the Ovarian Vein. Issue 8 (1st October 2014) - Ashihara, Keisuke; Tanaka, Tomohito; Maruoka, Risa; Ono, Yoshihiro J.; Tanabe, Akiko; Terai, Yoshito; Ohmichi, Masahide
Abstract : Objective: Type 1 endometrial cancer (EC) is typically sex hormone sensitive; however, most women diagnosed with EC have already gone through menopause. Several studies have reported that the postmenopausal ovary is hormonally active, and estradiol (E2) production from the ovaries persists for as much as 10 years beyond menopause. The aim of this study was to evaluate whether sex steroid production from the ovaries contributes to the pathogenesis of type 1 EC. Materials and Methods: This was a prospective study of 53 women treated for EC (28 cases of type 1 disease and 25 cases of type 2 disease). Serum specimens were collected from the peripheral and ovarian veins of participants undergoing bilateral oophorectomy. The sex steroid hormone levels and hormonal milieu on cervical cytology were evaluated as maturation value (MV). In addition, the degree of stromal hyperplasia of the ovary was evaluated histologically. Results: Although the E2 levels of the peripheral veins did not show any significant differences [8.2 (5.1–12.4) vs 7.4 (5.1–11.7) pg/mL, respectively; P < 0.05], the patients with type 1 EC had a higher E2 level in the ovarian vein than those with type 2 EC [25 (13.8–42.5) vs 15 (10.0–23.0) pg/mL, respectively; P < 0.05]. There were also no significant differences in the rate of moderate to marked hyperplasia of the ovarian stroma between the groups; however, the thickness of the ovarian cortex demonstrated a correlation with the ovarian E2 level. In addition, the MV displayed a strong correlation with the ovarian E2 level, but not the peripheral E2 level. Conclusions: The postmenopausal ovary is hormonally active, especially in patients with type 1 EC. The degree of ovarian stromal hyperplasia may (at least in part) contribute to the progression of type 1 EC, and MV may predict the level of E2 production from the ovaries in postmenopausal women.